2021
DOI: 10.1186/s12955-021-01902-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of moderate-to-severe psoriasis on quality of life in China: a qualitative study

Abstract: Purpose Psoriasis is a serious health problem. Since limited research has investigated the impact of psoriasis on the quality of life of patients with moderate-to-severe psoriasis, this study aimed to explore this issue. Methods A qualitative study was conducted with 22 psoriasis patients from two cities in Shandong province of eastern China participating in one-to-one semi-structured in-depth interviews. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…However, a notable proportion also had negative attitudes. This supports previous research showing that patients with psoriasis often experience negative emotions, social exclusion, and stigmatization ( 27 – 29 ). However, other studies have reported positive attitudes among patients who actively seek treatment and engage in self-care practices, leading to better quality of life ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, a notable proportion also had negative attitudes. This supports previous research showing that patients with psoriasis often experience negative emotions, social exclusion, and stigmatization ( 27 – 29 ). However, other studies have reported positive attitudes among patients who actively seek treatment and engage in self-care practices, leading to better quality of life ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 92%
“…The study examined many aspects of patients' lives that psoriasis affected including the symptoms, management of the symptoms, functioning, activities of daily living, psychological and social impact, as well as finances and employment. The findings of the study demonstrated that psoriasis had a negative impact on patients' lives and lowered the QoL (Zhong et al, 2021).…”
Section: Discussionmentioning
confidence: 86%
“…IL-23, IL-12, and IL-17 have increasingly become new target molecules as research has progressed [25]. Studies have demonstrated that the IL-23 and IL-12 receptor antagonists, risankizumab and ustekinumab, could improve patients' well-being with psoriasis and the main outcomes for the assessment of the clinical effects include PASI and Dermatology Life Quality Index (DLQI) [26][27][28]. LOTUS [29], a phase-III clinical trial with 322 Chinese participants, is aimed at evaluating the effect of ustekinumab on moderate to severe psoriatic patients, and the results suggested that at week-12, the PASI75 reaction in patients receiving ustekinumab 45 mg (82.5%) was significantly higher than those who received placebo (11.1%).…”
Section: Discussionmentioning
confidence: 99%